Personal dispositions explain differences in physical health benefits of nature exposure: the role of restorativeness and affect - Russo, Claudia; Romano, Luciano; Spano, Giuseppina; Theodorou, Annalisa; Carrus, Giuseppe; Mastandrea, Stefano; Angelini, Cinzia; Sanesi, Giovanni; Panno, Angelo (Frontiers in Psychology, 2024)
Introduction. Urbanization processes are constantly increasing, and most of the European population currently live in urban areas. Nevertheless, evidence is consistent in highlighting the positive association between nature exposure and human wellbeing, although individual differences might affect this association. Methods. The present study aimed to investigate the association among nature connectedness, conceptualized as Love and Care for Nature, place identity, and physical wellbeing, via restorativeness and positive and negative affect. A total of 312 visitors of an urban green area (i.e., Milan's Parco Nord) participated in the study. They completed an anonymous selfreport questionnaire. Results. Findings showed that nature connectedness and place identity positively affect physical wellbeing, via restorativeness and positive affect, but not through the negative ones. Discussion. Results highlight the importance of the joint role of exposure to nature and individual differences in promoting wellbeing. This study offers implications for interventions aimed at enhancing individuals' health through exposure to nature. Limitations of the study, and future research developments, and practical implications of the results are discussed.